Chemo-sorption nonwoven textile materials for purification of waste waters containing Cu** - Margarita Neznakomova; M.L. Klotz (Zaštita Materijala, 2016)
Proposed is a method and product for UV radiation modification of the surface of the needle-felted non-woven metrerial from polyethylene terephthalate standard fibers, for obtaining of ion exchange filters. The fibers obtained should possess a 3D structure and a high hydrolytic stability, which has to guarantee their multiple usage during the numerous sorption processes. As surface modifiers are used Polyethilenimine (PEI), grafted on the surface of the PET fibers with the Epichlorhydrin, Dimethylol dihydroxy cyclic ethylene urea (DMDHEU- C5H10N2O5, Glyoxal (C2H2O2).5. The filter materials obtained are highly effective towards the retention of Cu2+ from industrial waste waters.